Pembuatan Busana Fantasi Variasi Bordir India Dengan Sumber Ide Bangunan Taj Mahal - Mien Zyahratil Umami; Nisa’ Aulia Fitriani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2023)
Fantasy dress inspired by the shape of the dome of the Taj Mahal with the addition of Indian embroidered applications featuring typical Indian clothing. The problem raised in the making of this Final Project is how is the Process of Making Fantasy Clothing of Indian Embroidery Variation Using the Source of the Taj Mahal Building Idea? and how to apply variations of Indian embroidery on fantasy clothing?. The purpose of this study was to determine the process of making Indian embroidery variations of fantasy clothing with the taj mahal building as the source of the idea and to determine the application of Indian embroidery variations to fantasy clothing. The method used is observation method, documentation method, library method and data analysis.The process of making this fantasy dress goes through several stages, namely: determining the fashion design, preparing tools and materials, taking measurements, making patterns, cutting the material on the main material, pressing the coating material on the main material, merging, sewing, finishing. While the embroidery on this fantasy dress uses the Zari motif which is a symbol of luxury and elegance. The process of applying embroidery goes through several stages, namely: determining the design, preparing tools and materials, quoting the design, making embroidery on other materials, the process of applying embroidery to clothing, finishing.To produce neat crop top tile wrinkles, it is finished using a small som. The process of installing a skirt or peplum waistband is done by pulling the lower part to adjust the upper part so that it fits the expected design.